Hadith Representation in Film: A Hermeneutical Analysis of Ipar Is Death Based on Yusuf Qardhawi’s Approach - Khasanah, Isnatul; Friyadi, Arif (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
This study analyses the film Ipar Adalah Maut in the context of the interpretation of the hadith that inspired the story, focusing on the descriptive method and the hermeneutical approach proposed by Yusuf Qardhawi. The purpose of this study is to explore the strengths and weaknesses of hadith representation in the film as well as its impact on audience understanding. The descriptive method was used to collect and analyse data from the film as well as scholars' views on hadith interpretation. The results show that the film has the potential to convey a moral message, but also faces challenges in terms of accuracy and representation that may affect people's understanding of Islamic teachings. Qardhawi's hermeneutic approach emphasises the importance of understanding the social and cultural context in the interpretation of hadith, so as to bridge the gap between religious texts and current social realities. The conclusion of this study emphasises the importance of media as a tool of da'wah that can spread the teachings of Islam in a constructive and educational manner